Galectin‐1 is essential for the induction of MOG35–55‐based intravenous tolerance in experimental autoimmune encephalomyelitis. Issue 7 (25th May 2016) - Mari, Elisabeth R.; Rasouli, Javad; Ciric, Bogoljub; Moore, Jason N.; Conejo‐Garcia, José R.; Rajasagi, Naveen; Zhang, Guang‐Xian; Rabinovich, Gabriel A.; Rostami, Abdolmohamad
Abstract : Intravenous injection of MOG35–55 increases synthesis of galectin‐1. Galectin‐1 binds to DCs and induces IL‐27, TGF‐β1, and IL‐10 inducing a tolerogenic phenotype. Tolerogenic DCs promote the generation of Tr1 cells and the expansion of Treg cells, which downregulate proinflammatory responses and suppress EAE. Abstract : In experimental autoimmune encephalomyelitis (EAE), intravenous (i.v.) injection of the antigen, myelin oligodendrocyte glycoprotein‐derived peptide, MOG35–55, suppresses disease development, a phenomenon called i.v. tolerance. Galectin‐1, an endogenous glycan‐binding protein, is upregulated during autoimmune neuroinflammation and plays immunoregulatory roles by inducing tolerogenic dendritic cells (DCs) and IL‐10 producing regulatory type 1 T (Tr1) cells. To examine the role of galectin‐1 in i.v. tolerance, we administered MOG35–55 ‐i.v. to wild‐type (WT) and galectin‐1 deficient ( Lgals1 −/− ) mice with ongoing EAE. MOG35–55 suppressed disease in the WT, but not in the Lgals1 −/− mice. The numbers of Tr1 cells and Treg cells were increased in the CNS and periphery of tolerized WT mice. In contrast, Lgals1 −/− MOG‐i.v. mice had reduced numbers of Tr1 cells and Treg cells in the CNS and periphery, and reduced IL‐27, IL‐10, and TGF‐β1 expression in DCs in the periphery. DCs derived from i.v.‐tolerized WT mice suppressed disease when adoptively transferred into mice with ongoing EAE, whereas DCs from Lgals1 −/− MOG‐i.v. mice were not suppressive. These findings demonstrate that galectin‐1 is required for i.v. tolerance induction, likely via induction of tolerogenic DCs leading to enhanced development of Tr1 cells, Treg cells, and downregulation of proinflammatory responses.